Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3847/1538-4357/aa72f6
|View full text |Cite
|
Sign up to set email alerts
|

Complex Organic Molecules toward Embedded Low-mass Protostars

Abstract: Complex organic molecules (COMs) have been observed towards several low-mass young stellar objects (LYSOs). Small and heterogeneous samples have so far precluded conclusions on typical COM abundances, as well as the origin(s) of abundance variations between sources. We present observations towards 16 deeply embedded (Class 0/I) low-mass protostars using the IRAM 30m telescope. We detect CH 2 CO, CH 3 CHO, CH 3 OCH 3 , CH 3 OCHO, CH 3 CN, HNCO, and HC 3 N towards 67%, 37%, 13%, 13%, 44%, 81%, and 75% of sources… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
97
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 53 publications
4
97
2
Order By: Relevance
“…The two sources of Bergner et al (2017) with detections of CH 3 OCH 3 and CH 3 OCHO have abundances relative to methanol of ∼0.09 and ∼0.06 for these two molecules, respectively, which is similar to what we obtain for group 3 for both molecules and group 2 for CH 3 OCH 3 , but a factor 3-5 higher than group 1 (Table 7). In addition, Bergner et al (2017) report a median value of CH 3 CHO abundance relative to methanol similar to the values of groups 2 and 3 but a factor ∼5 higher than group 1. Group 1 may thus represent sources that have undergone a different type of chemical processing of O-bearing COMs on small scale compared to the dominant processing in the cold envelope.…”
Section: Comparison To Other Com Surveyssupporting
confidence: 85%
See 4 more Smart Citations
“…The two sources of Bergner et al (2017) with detections of CH 3 OCH 3 and CH 3 OCHO have abundances relative to methanol of ∼0.09 and ∼0.06 for these two molecules, respectively, which is similar to what we obtain for group 3 for both molecules and group 2 for CH 3 OCH 3 , but a factor 3-5 higher than group 1 (Table 7). In addition, Bergner et al (2017) report a median value of CH 3 CHO abundance relative to methanol similar to the values of groups 2 and 3 but a factor ∼5 higher than group 1. Group 1 may thus represent sources that have undergone a different type of chemical processing of O-bearing COMs on small scale compared to the dominant processing in the cold envelope.…”
Section: Comparison To Other Com Surveyssupporting
confidence: 85%
“…Group 1 may thus represent sources that have undergone a different type of chemical processing of O-bearing COMs on small scale compared to the dominant processing in the cold envelope. The situation is less clear for the N-bearing COMs: the CH 3 CN abundances relative to methanol derived by Bergner et al (2017) range from 0.005 to 0.05, which encompasses the values we derive for the three groups of the CA-LYPSO sample. Bergner et al (2017) found that methanol is well correlated with CH 3 CHO and CH 3 CN in their source sample.…”
Section: Comparison To Other Com Surveyssupporting
confidence: 44%
See 3 more Smart Citations